Awareness of dairy farmers about antibiotic resistance in Eastern Haryana region - Kumar, Vikash; Gupta, Jancy (Indian Journal of Dairy Science, 2018)
In an attempt to trace the dairy farming practices in relation to antibiotic resistance, the awareness levels of dairy farmers regarding antibiotic resistance were assessed. Eastern Haryana region, comprising of Karnal and Kurukshetra districts were purposively selected, and four villages from each district were selected randomly. From each village, 21 farmers were selected using stratified random sampling by categorizing into small, medium, and large farmers were taken in the study constituting a total of 168 farmers as respondents. An antibiotic resistance awareness index (ARAI) was developed in order to assess their level of awareness regarding antibiotic resistance. The study revealed that small farmers were least aware about antibiotic resistance because of immediate focus to cure bacterial disease, irrespective of antibiotic or other class of drug. Medium holder dairy farmers were able to realise the greater effectiveness of antibiotic over other drugs in treatment. They recognised the level of inefficiency and declining effectiveness of antibiotics to cure disease aggravating the antibiotic resistance. Large dairy farmers were most aware about the antibiotic resistance, and expressed much concern about the judicious use of antibiotics and managed the large scale use of antibiotics judiciously at herd level. Results suggested that familiarity of antibiotic in relation to environmental impacts and transfer of antibiotic resistance among species through milk and its products were least among all the categories of farmers. Thus, insight in to awareness level of farmers could be imperative to establish surveillance and have foremost priority in antibiotic conservation related policy formulation.